STRUCTURE OF MANGROVE VEGETATION IN MANGKANG WETAN VILLAGE, TUGU DISTRICT, SEMARANG CITY - Ismail, R. Mohamad; Widayanti, Dhiya Artika; Wardono, Suko (Universitas Mataram, 2025)
Mangroves are coastal vegetation characterized by distinctive root morphology and adapted to tidal environments. They play a vital role as providers of organic matter and represent a natural resource utilizable by local communities. The objective of this study was to determine the mangrove community structure in Mangkang Wetan Village, Tugu District, Semarang City. The research was conducted from July to September 2024 across three observation stations within Mangkang Wetan Village. Analysis of mangrove community structure employed the purposive sampling method using a line transect with 10 x 10 m plots, replicated three times. The results of the mangrove community structure analysis in Mangkang Wetan Village identified only one mangrove species: Avicennia marina, present at the tree vegetation level. This species was selected as it is readily available in the surrounding natural mangrove forest, easily cultivated, and its stands provide significant resistance to coastal abrasion. Consequently, the study location constitutes a monospecific (homogeneous) mangrove forest. The Importance Value Index (IVI) for mangroves at stations 1, 2, and 3 was consistently 300. The mangrove species diversity level in Mangkang Wetan Village was recorded with a Shannon-Wiener Diversity Index (H') value of 0, indicating relatively low species diversity. The species evenness index values at stations 1, 2, and 3 were also 0, reflecting low species evenness. The dominance index (C) value was 1, signifying the dominance of a single species. The low diversity and evenness values are attributed to the relatively uniform or homogeneous condition of the mangrove forest.